The Effect Of Lapse Of Time In A Criminal Case From The Perspective Of Islamic Jurisprudence And The Criminal Law Of Afghanistan (Eurasian Journal of Learning and Academic Teaching, 2024)
Elapse of time means the passing of a certain time on the criminal case or the application of punishment. The same period that is discussed in Islamic jurisprudence under the title (Taqadam). The problem mentioned in the current era is that the criminal case is presented to the court after a long time. Can such a claim be heard or not? And what effect does the passage of time have on this? The importance of the research is that in the current era, lawsuits arise over some cases that have been pending for a long time and the claimant presents her lawsuit to the court without any valid excuse, which is a problem. So how can we solve this problem? This research has discussed and examined the aspects of this issue in a specialized way, comparing it with jurisprudence and law.